A global player from the South: the Jardín Zoológico de Buenos Aires and the transnational network of zoos in the early twentieth century - Oliver Hochadel (História, Ciências, Saúde: Manguinhos, 2022)
Abstract Under the directorship of Clemente Onelli (1904-1924), the Jardín Zoológico de Buenos Aires became a major public attraction and gained an international reputation for its innovations in animal keeping and as a supplier of Latin American fauna. It was a hybrid institution that combined the tasks of public instruction, zoological research, and acclimatization of useful animals, and also served as a symbol of national pride. Despite its seemingly peripheral geographical location, the institution was firmly integrated in the global network of zoological gardens. This paper utilizes a transnational perspective to tease out the numerous, multidirectional exchanges of animals and knowledge between the Jardín Zoológico de Buenos Aires and Northern metropolises.